Making Systems Thinking Accessible for Qualitative Researchers: A Primer on Systems Thinking and Introducing Inductive Systemic Analysis - Alexandra van Beek; Janya McCalman; Vicki Saunders (International Journal of Qualitative Methods)
Systems thinking is a paradigm well-suited to complex social and health fields such as socioeconomic approaches to wellbeing and health intervention research. Yet despite increasing calls for more general application of systems thinking in these fields of research, the paradigm remains poorly understood and systemic analysis is rare, particularly in qualitative research. This paper aims to address these issues. It starts by providing a primer to systems thinking clarifying what systems thinking is as a research philosophy, and describing core systemic principles such as complex causality and emergence. It then introduces the novel method of Inductive Systemic Analysis. Combining the methodology of grounded theory with the principles and key concepts of systems thinking, this method was specifically designed to make systemic analysis both relatable and accessible to a wide range of qualitative researchers. Utilising the case example the method was developed with, the paper works through each step of the research process. It explains preparing for systemic research through boundary considerations and developing a systemic research question; and goes on to describe the four-step analytical process of “zooming in” and “zooming out”, exploring the data in different ways. Ultimately, the method aims to support researchers in finding a balance between reflecting the complexity of social situations with ease of comprehension and applicability.